THE RELATIONSHIP BETWEEN THE QUANTITY AND QUALITY OF ANTENATAL CARE AND NEWBORN OUTCOMES - Anjela Fatma Lovely (Yayasan Pendidikan Medika Indonesia, 2025)
Antenatal Care (ANC) is a pregnancy examination that aims to monitor maternal health and fetal development, detect abnormalities in pregnancy and childbirth, and plan healthy childbirth so as to prevent maternal and infant mortality. ANC examination according to the standard is carried out at least 6 times which includes 10T. ANC examination that’s not in accordance with the standard can increase the risk of LBW and neonatal asphyxia. The purpose of this study was to analyze the relationship between the quantity and quality of ANC with newborn outcomes at Kediri Public Health Center. This study used a cross-sectional method with data taken from maternal and child health (KIA) books and interviews. A total of 31 respondents who visited posyandu (integrated health service post) in the Kediri Public Health Center’s working area were taken using non-probability sampling method. Spearman correlation test showed that correlation between quantity and quality of ANC with infant’s birth weight were p = 0.004 and p = 0.022 (p<0.05) for each. In addition, p = 0.004, p = 0.006, and p = 0.038 was obtained in the relationship between timeliness of ANC visits and case management during ANC with infant’s birth weight, and giving blood supplement tablets during ANC with asphyxia. It can be concluded that there is a relationship between quantity and quality of ANC with infant’s birth weight, timeliness of ANC visits with infant's birth weight, case management during ANC with infant's birth weight, and giving blood supplement tablets during ANC with the neonatal asphyxia.